Acting up or opting out? Truancy in Irish secondary schools - Merike Darmody; Emer Smyth; Selina McCoy (The Economic and Social Research Institute (ESRI), 2007)
This paper explores the way in which truancy levels are structured by individual social class and the social mix of the school within the Republic of Ireland. Drawing on a national survey of young people, truancy levels are found to be higher among working-class and Traveller students. Truancy is more prevalent in predominantly working-class schools, mainly because young people see them as less supportive and more disorderly environments. The empirical analyses are situated within the context of the concepts of individual and institutional habitus as well as resistance theory. Our findings suggest the institutional habitus of the school is a strong factor in influencing truancy levels among young people. While truancy operates as a form of student resistance to the school system, it serves to reproduce social class inequalities since it is associated with more negative educational and labour market outcomes in the longer term.
Keywords: 330; Bildungsverhalten; Soziale Lage; Schüler; Allgemeinbildende Schule; Schätzung; Irland